Apistogramma ortegai (Teleostei: Cichlidae), a new species of cichlid fish from the Ampyiacu River in the Peruvian Amazon basin - Britzke, Ricardo; Oliveira, Claudio; Kullander, Sven O. (Zootaxa, 2014)
Apistogramma ortegai, new species, is described from small streams tributaries of the Ampiyacu River near Pebas, in eastern Peru. It belongs to the Apistogramma regani species group and is distinguished from all other species of Apistogramma by the combination of contiguous caudal spot to bar 7, presence of abdominal stripes, short dorsal-fin lappets in both sexes, absence of vertical stripes on the caudal fin, and reduced number of predorsal and prepelvic scales.